Assessment of the knowledge of Dentistry students about oral cancer, a cross-cutting study (Research, Society and Development, 2021)
Introduction: Cancer is the name given to more than 100 types of diseases that affect tissues and organs, due to the disordered growth of cells. There are about 626,000 new cases of cancer for the year 2020 in Brazil, excluding non-melanoma skin cancer. Objective: The objective of this study was to evaluate the knowledge of dental students regularly enrolled at Centro Universitário Unifacvest, located in the city of Lages/SC, in 2020, about oral cancer. Methodology: A questionnaire was applied to 199 students regularly enrolled in the dentistry course at Centro Universitário Unifacvest, in the phases that perform clinical care from the fifth to the tenth period, in February and September 2020. Data were collected, analyzed and accounted for in spreadsheets. Afterwards, descriptive statistics were performed using absolute frequencies and percentages of variables related to the characterization of students and answered questions. Results: A total of 199 students participated in the study, with a predominantly female sample of 71.4%, which was categorized by non-integrated clinic with a total of 62 students and integrated clinic with a total of 135 students. Conclusion: Therefore, based on the results presented, we conclude that the students' knowledge is positive, in addition to the importance of the dentist in the diagnosis of oral cancer. We point out the importance of prevention, as well as the discipline of oral pathology, together with the integrated clinic.